Normative Study On Criminal Liability Of The Captain For The Occurrence Of A Fatal Accident That Causes The Death Of A Person - Satria Wibawa, Zakka; Lulu Hawazien, Asri; Maulana, Areza; Harmono, Harmono; Waluyadi, Waluyadi (Ann Publisher, 2024)
The purpose of this study is to describe criminal liability for the captain for the occurrence of fatal accidents that cause the death of people. The method provided uses a data normative law research approach using secondary data and techniques with document and literature studies. The study results show that the captain is the highest leader on a ship and is responsible for the occurrence of ship accidents unless it can be proven otherwise. The captain's criminal liability for a fatal accident is caused by technical, human, and natural factors. Ship accidents caused by technical and human factors result from a lack of caution (negligence) or a mistake. Because of the fulfillment of the elements of criminal liability, namely mistakes (schuld), being able to take responsibility, and the absence of excuses, the captain is burdened with criminal liability. Meanwhile, ship accidents caused by natural factors are included in noodtoestand. This force majeure circumstance is a reason for forgiveness in criminal law so that the captain is not burdened with criminal liability.